DNA damage in wistar kyoto rats exercised during pregnancy - Corrêa, Mikaela da Silva [UNESP]; Gelaleti, Rafael Bottaro [UNESP]; Bento, Giovana Fernanda [UNESP]; Damasceno, Débora Cristina [UNESP]; Peraçoli, José Carlos [UNESP] (FapUNIFESP (SciELO), 2017)
Purpose: To evaluate DNA damage levels in pregnant rats undergoing a treadmill exercise program. Methods: Wistar Kyoto rats were allocated into two groups (n= 5 animals/group): non-exercise and exercise. The pregnant rats were underwent an exercise protocol on a treadmill throughout pregnancy. Exercise intensity was set at 50% of maximal capacity during maximal exercise testing performed before mating. Body weight, blood pressure and glucose levels, and triglyceride concentration were measured during pregnancy. At day 10 post-natal, the animals were euthanized and maternal blood samples were collected for DNA damage. Results: Blood pressure and glucose levels and biochemical measurements showed no significant differences. Increased DNA damage levels were found in exercise group compared to those of non-exercise group (p<0.05). Conclusion: The exercise intensity protocol used in the study might have been exhaustive leading to maternal increased DNA damage levels, demonstrating the relevance of an adequate protocol of physical exercise.
Keywords: DNA damage; Exercise; Pregnancy; Rats